Perception and action about food security: a case study of family farmers in Vitorino/PR (Research, Society and Development, 2021)
The predominance of Brazilian land occupied by commodity crops presents a production model that threatens the country's food security and sovereignty. Thus, the practice of production for self-consumption emerges as a strategy to guarantee food security for rural families. It is all types of production carried out within the family unit, which is used by family members in order to meet their needs.  In this context, this article aims to understand the production for self-consumption, as well as the perception of family farmers on the issue of food security in the municipality of Vitorino/PR. Qualitative research was conducted with the support of participatory training meetings and the use of the participant observation method, and semi-structured interviews were applied with twenty-two family farmers in the municipality. The data presented show the importance of production for self-consumption in the face of the need to combat food and nutritional insecurity in the country, especially in the rural area, which has undergone many transformations. The concern with poison in food was very present in the narratives, so that food produced with pesticides or industrialized is perceived as synonymous with food that produces insecurity of consumption, besides being a health risk.